Complementary feeding practices among infants aged 6-12 months in selected health clinics in Selangor / Huwaina Abdullah ... [et al.] - Abdullah, Huwaina; Mt Yusof, Mardziah; Omar, Muhammad Faris; Mohd Sobri, Syafiqah (2014)
Complementary feeding practices should start at the age of six months along with breastfeeding in order to promote a proper growth and development of infants. This cross-sectional study was aimed to investigate the complementary feeding practices among infants aged 6 to 12 months in selected health clinics in urban and rural area of Selangor. A total of 109 infants participated in this study. The anthropometry values taken were weight, length, body mass index (BMI), mid upper arm circumference (MUAC) and head circumference. The diet intake was obtained by using 2 days (1 weekday and 1 weekend) of 24-hour diet record and the results were later compared with Malaysian Recommended Nutrient Intake (RNI) and the recommendation of complementary feeding by World Health Organization (WHO). Out of 109 participants, 94.5% (n^=103) have started complementary feeding while another 5.5% (n=6) were still exclusively breastfed without starting complementary feeding. Out of 103 infants who have started complementary feeding, 27.2% (n=28) of them still breastfed, 36.9% (n=38) are bottle fed while another 35.9% (n=37) infants were both breastfed and bottle fed.